Application of ecological indices using macroinvertebrate assemblages in relation to aquaculture activities in Rawang sub-basin, Selangor River, Malaysia - Hettige, Nadeesha Dilani; Hashim, Rohasliney; Abas Kutty, Ahmad; Jamil, Nor Rohaizah; Ash'aari, Zulfa Hanan (Universiti Putra Malaysia Press, 2021)
This study aimed to evaluate benthic macroinvertebrates assemblages using the application of ecological indices in the Rawang sub-basin of the Selangor River with reference to determining the impacts of aquaculture practices on benthic macroinvertebrates. In total, seven sampling sites were selected, namely Guntong (SR1), Guntong’s tributaries (SR2, control site), Kuang (SR3 and SR7), Gong (SR4), Buaya (SR5) and Serendah (SR6) Rivers. Sites were selected using a random sampling technique and the accessibility and proximity to aquaculture farms. Macroinvertebrates were sampled from April 2019 to March 2020 using an aquatic kick net, a hand spade, and a D-frame dip net. Water samples were also taken. Twenty-seven families belonging to the Annelida, Mollusca and Athropoda phyla were identified using taxonomic keys. Tubificidae was found to be the most dominant family (36.79%) followed by Chironomidae (28.84%). The highest number of individuals from family Tubificidae was recorded in Gong River, where effluent was discharged from an aquaculture farm. The total abundance of benthic macroinvertebrates increased with increased proximity to the aquaculture farm. Based on Biological Monitoring Working Party score value, the water quality of sampling sites in close proximity to the aquaculture farm was polluted as compared to the control location. Family Biotic Index score showed that all sites were substantially polluted with organic pollution, with the control site being much less polluted. In conclusion, benthic macroinvertebrates assemblage was affected by effluent originating from aquaculture farm outlets. It is therefore necessary to conduct aquaculture farming using methods that are deemed to be environmentally friendly.